2022
DOI: 10.1002/admi.202201648
|View full text |Cite
|
Sign up to set email alerts
|

Tapered Cross Section Photoelectron Spectroscopy Provides Insights into the Buried Interfaces of III‐V Semiconductor Devices

Abstract: Interfaces are key elements that define electronic properties of the final device. Inevitably, most of the active interfaces of III–V semiconductor devices are buried and it is therefore not straightforward to characterize them. The Tapered Cross Section Photoelectron Spectroscopy (TCS‐PES) approach is promising to address such a challenge. That the TCS‐PES can be used to study the relevant heterojunction in epitaxial III–V architectures prepared by metalorganic chemical vapor deposition is demonstrated here. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…However, performing PES on these interfaces requires accessing them without modifying the characteristics of the device. [ 6 ] Accessing the interfaces by preparation and investigation of a normal cross section is not feasible due to low lateral resolution of standard PES set‐up (i.e., above 10 μm and up to several hundreds of micrometers) compared with the thickness of typical perovskite solar cells and especially with the extensions of the space charge regions within. Approaches to overcome this limitation exist and can be classified as bottom‐up or top‐down approaches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, performing PES on these interfaces requires accessing them without modifying the characteristics of the device. [ 6 ] Accessing the interfaces by preparation and investigation of a normal cross section is not feasible due to low lateral resolution of standard PES set‐up (i.e., above 10 μm and up to several hundreds of micrometers) compared with the thickness of typical perovskite solar cells and especially with the extensions of the space charge regions within. Approaches to overcome this limitation exist and can be classified as bottom‐up or top‐down approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This was the case for III‐V semiconductor devices (e.g., GaInP on Ge and GaAs substrates) that were strongly disturbed by Fermi‐level pinning to the surface states created by the polishing procedure, also rendering it impossible to measure binding energy shifts due to illumination. [ 6 ] In contrast, perovskites with their shallow gap states are unaffected by this phenomenon and previous works have shown that it is possible to extract reliable information on the electronic properties of PSCs. [ 25 ] Moreover, the binding energies observed in TCS layers, along with their change under illumination, are in good agreement with previous measurements from half‐cells that were not subjected to the TCS‐preparation method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation